Engaging parenting through the multifuntional jacket bag baby Carrier / Sulaiman Mohd Shah and Sharifah Alwiah Syed Sahil - Mohd Shah, Sulaiman; Syed Sahil, Sharifah Alwiah (Universiti Teknologi MARA, 2018)
Multifunctional jacket bag baby carrier is designed to fulfil both aesthetic and functionality aspect of carrying babies. In this paper, the focus is the jacket bag baby carrier and the proper way of mass producing this product is also researched. This research is done to contribute the production processes of baby carrier outfit that can be applied by manufacturers, designers, and academia. Qualitative research method such as observation, interview and experimentation are mainly used to obtain data. Quantitative data is obtained via survey to identify the right design. The main advantage of this product is that it can fulfil the functionality and aesthetic category while also engaging parenting via proper baby positioning in the carrier that is conducive for parental bond formation.